Deficiency of the Circadian Clock Gene Bmal1 Reduces Microglial Immunometabolism - Wang, Xiao-Lan; Wolff, Samantha E. C.; Korpel, Nikita; Milanova, Irina; Sandu, Cristina; Rensen, Patrick C. N.; Kooijman, Sander; Cassel, Jean-Christophe; Kalsbeek, Andries; Boutillier, Anne-Laurence; Yi, Chun-Xia (Frontiers in Immunology, 2020)
Microglia are brain immune cells responsible for immune surveillance. Microglial activation is, however, closely associated with neuroinflammation, neurodegeneration, and obesity. Therefore, it is critical that microglial immune response appropriately adapts to different stressors. The circadian clock controls the cellular process that involves the regulation of inflammation and energy hemostasis. Here, we observed a significant circadian variation in the expression of markers related to inflammation, nutrient utilization, and antioxidation in microglial cells isolated from mice. Furthermore, we found that the core clock gene-Brain and Muscle Arnt-like 1 (Bmal1) plays a role in regulating microglial immune function in mice and microglial BV-2 cells by using quantitative RT-PCR. Bmal1 deficiency decreased gene expression of pro-inflammatory cytokines, increased gene expression of antioxidative and anti-inflammatory factors in microglia. These changes were also observed in Bmal1 knock-down microglial BV-2 cells under lipopolysaccharide (LPS) and palmitic acid stimulations. Moreover, Bmal1 deficiency affected the expression of metabolic associated genes and metabolic processes, and increased phagocytic capacity in microglia. These findings suggest that Bmal1 is a key regulator in microglial immune response and cellular metabolism.